E-066 Neonate high flow fistula embolization with high volume coil. (23rd July 2017) - Bohnstedt, B; Pandav, V; Dandapat, S; Williams, A
Abstract : Vein of Galen malformations and intracranial high flow pial arteriovenous fistulas are uncommon vascular malformations that present in neonates or early childhood. In the general population, Vein of Galen malformations constitute less than 1%–2% of all intracranial vascular malformations, but 30% of vascular malformations in pediatric patients (6). Intracranial pial arteriovenous fistulas account for 1.6%–8.4% of all intracranial vascular malformations, but 4% of intracranial vascular malformations in pediatric patients (4). The prevalence of intracranial pial arteriovenous fistulas is estimated to be 0.1/100, 000 to 1/100, 000 (5). There were 112 cases reported from 1977 to 2009 (4). Children often present in the first few days of life with high flow cardiac output failure or pulmonary hypertension and require treatment of these high flow vascular malformations for survival. Ethylene Vinyl-Alcohol (EVOH) and N-butyl cyanoacrylate (NBCA) glue are good embolic agents for the treatment of adult vascular malformations, but the fistulas in neonates are often as large as 3 mm in diameter which makes it difficult to reduce blood flow with one of these agents alone. We present a case series of 3 neonates who presented to our facility in high flow cardiac output failure or pulmonary hypertension within three days of life. The first child had a large right temporal pial arterial venous fistula (Fig 1a), and the second and third child had Vein of Galen malformations. Two patients had high flow cardiac output failure and one patient had pulmonary hypertension attributable to the intracranial fistula. Each patient was treated with high volume coils (0.020) with specific large vessel sacrifice using a Penumbra Occlusion Device (Fig 1b). We found that large volume coils offer safe reduction in flow, with the ability to control the embolization. These coils can also be used to provide a scaffold for EVOH or nBCA to complete flow arrest in individual vessels. During the procedure, two of the children had a reduction in required vasoactive agents and an improvement in oxygen saturation. The third child had an improvement in oxygen requirements and a reduction in B-type Natriuretic Peptide following embolization. This case suggests a novel, effective method for vessel sacrifice for high flow fistulas in neonates and reduces the cardiopulmonary effects of the fistula in the neonatal period. Disclosures: B. Bohnstedt: 1; C; Penumbra, Codman, Stryker. V. Pandav: None. S. Dandapat: None. A. Williams: None.